2020
DOI: 10.1021/acsami.0c09243
|View full text |Cite
|
Sign up to set email alerts
|

Gallium Doping Effects for Improving Switching Performance of p-Type Copper(I) Oxide Thin-Film Transistors

Abstract: Copper(I) oxide (Cu 2 O), which is obtained from copper(II) oxide (CuO) through a reduction process, is a p-type oxide material with a band gap of 2.1−2.4 eV. However, the switching performance of typical Cu 2 O thin-film transistors (TFTs) is poor because the reduction process increases the concentration of oxygen vacancies (V O ), which interfere with the conduction of hole carriers. Ga with high oxygen affinity was doped in Cu 2 O thin films to decrease V O during the reduction process. As a result, the V O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 34 publications
1
23
0
3
Order By: Relevance
“…18,22,39 In addition, it should be noted that the SS and on/off current ratio are preferably better than those from previously reported planar p-type transistors (Table S1, ESI †) and vertical n-type transistors. 40,41 The channel coating process provides extraordinarily good electrodeposition, and existing methods, such as conventional sputtering and sol-gel processes, cannot produce artificially vertically aligned GBs in the oxide channel layers.…”
Section: Electrical Properties Of the Sb Doped Cu 2 O Vertical Transi...mentioning
confidence: 99%
“…18,22,39 In addition, it should be noted that the SS and on/off current ratio are preferably better than those from previously reported planar p-type transistors (Table S1, ESI †) and vertical n-type transistors. 40,41 The channel coating process provides extraordinarily good electrodeposition, and existing methods, such as conventional sputtering and sol-gel processes, cannot produce artificially vertically aligned GBs in the oxide channel layers.…”
Section: Electrical Properties Of the Sb Doped Cu 2 O Vertical Transi...mentioning
confidence: 99%
“…Recent studies have mostly focused on copper oxide (CuO) semiconductors for electronics and energy devices because it offers the advantages of non-toxicity, cost-effectiveness, and abundance. To meet the demand for high-performance p-channel devices, Bae et al enhanced the performance of copper-based TFTs by doping the semiconductor film with gallium atoms to reduce oxygen vacancies, which are known to interfere with the conduction of hole carriers [14]. Moreover, Baig et al demonstrated that the doping of CuO with yttrium atoms could enhance the device performance [15].…”
Section: Introductionmentioning
confidence: 99%
“…The surface morphology of Al 2 O 3 with R RMS of 0.18 nm is shown in Figure S3b. Generally, a TFT based on a high- k dielectric material such as Al 2 O 3 as the GI performs well at a lower operating voltage. Figure c shows the thermogravimetric and differential thermal analysis (TG-DTA) to examine the thermal stability of the CTSGO precursor solution. TG-DTA was performed in a N 2 atmosphere with a heating rate of 10 °C min –1 .…”
Section: Resultsmentioning
confidence: 99%